فقه التوسط عند المالكية: قراءة سياسية في أصول وقواعد الإمام مالك رحمه الله - المرزوق, عماد (جامعة الوادي - University of Eloued, 2022)
تمّت صياغة هذا البحث، للإجابة عن إشكالية مركزة، تتمحور حول الجوانب المؤثرة في بناء شخصية الإمام مالك، وصقل تجربته السياسية، ثم تأثيرها المباشر على سلوكه السياسي الطارئ. تغيّت الدراسة: -على المستوى الشخصي: التعرّف على المرجعية الفكرية والفقهية لإمام دار الهجرة. -على المستوى المنهجي والموضوعي: تحرير أهم القواعد التي استند إليها الإمام مالك لتأسيس نظريته السياسية. من أبرز المناهج التي ارتكزت عليها هاته الدراسة: المنهج الإستقرائي: من خلال تتبع النصوص المختلفة: تاريخية، وحديثية، فقهية...، كانت موضوع نظر الإمام مالك واستدلاله. المنهج التحليلي: حرصت على تحليل كافة النصوص المستقراة، مع وضعها في سياقها، التاريخي، المنشئ لفقه سياسي رشيد، إتّسم بالواقعية، واحتكم لما تقرّر قطعا من نصوص وقواعد شرعية مرعيّة. المنهج التاريخي: بما أن الإمام مالك، قد عاصر ثلاثة عشر خليفة، وتأثر بخمسة طبقات من فقهاء المدينة وعلمائها، فإن التعمق في هذه الجزئية سيتيح لنا فهم العقيدة السياسية التي تشكّلت لدى إمامنا مالك رحمه الله. حرصت في ختام هذه الدراسة صياغة جملة توصيات، وذلك من خلال: - الرجوع لمنهج إمام دار الهجرة في معالجة مسائل ذات صبغة سياسية محضة. - اِحتكام أيّ سلوك سياسي لبناء قواعدي تشريعي، يهيئُ للفتوى السياسية المناسبة:تدبيرا، وتنظيما، وترشيدا، أرضية نظرية وعملية مناسبة، صالحة للعمل والإعمال. - إسعاف الباحثين للتدبّر في هذا النموذج من الدراسات بغرض التعمق في فلسفة التشريع السياسي المصلحي عند الامام مالك، المحقّق للمناطات والمستجيب للحاجيات، والمُوجِد للتفاعل المطلوب بين النص والواقع، الوحي والتاريخ. ملخص البحث باللغة الإنجليزية The jurisprudence of moderation according to the Malikis: A political reading in the origins and rules of Imam Malik, may God have mercy on him. Imad El Merzouk. This research was formulated to answer a central problem revolving around the influential aspects in building and refining Imam Malik's political experience, and then its direct impact on his political behavior. The study aims to: On a personal level: Getting acquainted with the intellectual and jurisprudential references of the Imam of the House of Hijrah. On the methodological and objective level: Editing the most important rules on which Imam Malik relied in establishing his political theory. Among the most important approaches adopted by this study are: The inductive approach: by following the various texts: the historical, the hadith, and the jurisprudence that were under the consideration of Imam Malik. The Analytical Approach: I was keen to analyze all the texts while placing them in their historical context, which is the basis of political jurisprudence that is characterized by realism and is based on what is decided by legitimate texts and studied rules. . Historical Method: Since Imam Malik was a contemporary of thirteen"khalifa", and was influenced by five groups of jurists and scholars of Medina, delving into this part will allow us to understand the political doctrine laid down by Imam Malik, may God have mercy on him. At the conclusion of this study, recommendations were made: The importance of the approach of the Imam of Dar Al-Hijrah in dealing with issues of a purely political nature. - That any political behavior must refer to legislative foundations that prepare for the appropriate political fatwa - a measure, organization - rationalization. A suitable theoretical and practical ground for work and practice. - Helping researchers to think about this model of studies to delve into the philosophy of political reform legislation according to Imam Malik, who investigates the circumstances, responds to needs, and creates the required interaction between the text, reality, revelation, and history.
The jurisprudence of moderation according to the Malikis: A political reading in the origins and rules of Imam Malik, may God have mercy on him.
مقال
Keywords: المالكية، فقه التوسط، السياسة، المصلحة المرسلة، القوعد الفقهيةا; Malikis; Jurisprudence of mediation; Politics; The public interest; General Rules.